(untitled) (International Journal of Current Engineering and Technology, 2014)
L-Alaninium Succinate (LAS) single crystals were grown by slow evaporation method. The Vicker’s microhardness test was carried out on the grown crystal. The dielectric studies are carried out and the nature of variation of dielectric constant and dielectric loss in the frequency range of 50 Hz to 5 MHz at different temperatures (30ºC, 60ºC and 90ºC) is studied and reported. Photoconductivity measurements were carried out on the grown crystal reveals the negative photoconducting nature.